Plainsman Canola - Rife, Charlie L.; Shroyer, James P. (My University, 1999)
An informational publication about Plainsman canola, the first winter canola variety developed by the Kansas Agricultural Experiment Station.
L916_1999-05
Keywords: L916; Crops; L